Three‐dimensional FDTD modeling of neurons to solve EEG and MEG forward problem. Issue 4 (20th November 2017) - Hashemi, Soheil; Abdolali, Ali
Abstract: Neuronal activities including calcium sodium current, ligands current, and synaptic transmembrane current create electromagnetic fields. Here, an analytic method is suggested to obtain the electromagnetic fields and potential signals resulting from the function of nerve cells inside the brain. Modeling simulates the behavior of cells three‐dimensionally. The proposed method employs the electric scalar potential and magnetic vector potential to solve the time‐domain three‐dimensional equations using the partial differential method. All ion flows are considered as electrical current densities. In this method, the brain and desired cells are meshed to solve the problem using the numerical method. As an example, the electric fields, magnetic fields, and signals generated by cingulum nerve fibers are illustrated and compared in Cz, Fz, and T 3 electrode positions. A direct analysis method based on the same mechanism and biophysics of the nervous system is proposed. Employing this direct method leads not only to a better understanding of neuronal activity but also to a more accurate vision regarding the accuracy/inaccuracy of experimental and inverse methods. The analysis of these data provides insights into the brain function processes.